2005
DOI: 10.1038/nature03514
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for 5′-end-specific recognition of guide RNA by the A. fulgidus Piwi protein

Abstract: RNA interference (RNAi) is a conserved sequence-specific gene regulatory mechanism 1-3 mediated by the RNA-induced silencing complex (RISC), which is composed of a single-stranded guide RNA and an Argonaute protein. The PIWI domain, a highly conserved motif within Argonaute, has been shown to adopt an RNase H fold 4,5 critical for the endonuclease cleavage activity of RISC 4-6 . Here we report the crystal structure of Archaeoglobus fulgidus Piwi protein bound to double-stranded RNA, thereby identifying the bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
534
1
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 584 publications
(580 citation statements)
references
References 30 publications
41
534
1
4
Order By: Relevance
“…This result suggests that the Ago2 catalytic site can accommodate some siRNA:mRNA mismatches, in particular, combinations of mismatches that involve the smaller pyrimidine residues. There are no structural studies of Ago2, but two groups have crystallized the endonuclease domain of a homologous bacterial protein bound to a small siRNA-like duplex (17,18). Although the 5Ј end of the siRNA guide strand was well ordered in the crystal and embedded in the bacterial Piwi protein, the region corresponding to position 10 was disordered, suggesting that the active site may allow some flexibility for binding.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that the Ago2 catalytic site can accommodate some siRNA:mRNA mismatches, in particular, combinations of mismatches that involve the smaller pyrimidine residues. There are no structural studies of Ago2, but two groups have crystallized the endonuclease domain of a homologous bacterial protein bound to a small siRNA-like duplex (17,18). Although the 5Ј end of the siRNA guide strand was well ordered in the crystal and embedded in the bacterial Piwi protein, the region corresponding to position 10 was disordered, suggesting that the active site may allow some flexibility for binding.…”
Section: Discussionmentioning
confidence: 99%
“…The three-dimensional structures of bacterial and archaeal Argonaute proteins and the PAZ domains of eucaryotic Argonautes revealed that the PAZ domain binds the short single-stranded 3 0 'tails' characteristic of an siRNA. It has been postulated that the PAZ domain initiates incorporation of a small RNA into RISC by binding the single-stranded 2nt 3 0 overhang of an siRNA or miRNA duplexes (Lingel et al, 2003;Song et al, 2003Song et al, , 2004Yan et al, 2003;Ma et al, 2005). More remarkably, these structural studies revealed that the key to understanding the sequence-specific activity of RISC resides in the structure of the PIWI domain, whose three-dimensional fold clearly places in the RNase H enzyme family of nucleic-acid-directed RNA-endonucleases Ma et al, 2005;Parker et al, 2005;Yuan et al, 2005).…”
Section: Risc Formationmentioning
confidence: 99%
“…It has been postulated that the PAZ domain initiates incorporation of a small RNA into RISC by binding the single-stranded 2nt 3 0 overhang of an siRNA or miRNA duplexes (Lingel et al, 2003;Song et al, 2003Song et al, , 2004Yan et al, 2003;Ma et al, 2005). More remarkably, these structural studies revealed that the key to understanding the sequence-specific activity of RISC resides in the structure of the PIWI domain, whose three-dimensional fold clearly places in the RNase H enzyme family of nucleic-acid-directed RNA-endonucleases Ma et al, 2005;Parker et al, 2005;Yuan et al, 2005). This finding is consistent with earlier biochemical studies showing that chemistry of cleavage by human and fly RISC has many similarities to RNAse H-mediated catalysis: a requirement for the divalent cation Mg 2 þ and cleavage products with 5 0 terminal phosphates and 3 0 terminal hydroxyl groups (Martinez and Tuschl, 2004;Schwarz et al, 2004).…”
Section: Risc Formationmentioning
confidence: 99%
“…The Argonaute protein family is diverse, with all members containing a PAZ domain, which is involved in miRNA/siRNA binding, and a PIWI domain, which is related to RNaseH endonucleases and functions in slicer activity (Lingel and Sattler 2005). Argonaute proteins directly interact with the miRNA/siRNA (Song et al 2003;Ma et al 2004Ma et al , 2005. Most eukaryotes examined contain multiple Argonaute family members, with different Argonautes often specialized for distinct functions.…”
Section: Micro Rnas (Mirnas)/short Interfering Rnas (Sirnas) Are Impomentioning
confidence: 99%